Advanced deep drawing methods, challenges, and future scope - A Review - Rao, C. Jai Shiva; Lakshmi, K. Prasanna; Ramana, M. Venkata; Babu, Jalumedi (Universitas Muhammadiyah Magelang, 2024)
One of the important metal forming techniques employed in forming processes of sheet metal is deep drawing. This method allows to production of intricate shapes with fewer flaws. The quality of the deep-drawn product depends on the extent of control, exercised by the manufacturer, on process parameters of deep drawing. An effective end product with the least possible flaws can be manufactured using a deep drawing process by effectively controlling the process parameters. This article brings out a consolidated report of the research findings, as reported by researchers across the globe, on recent developments of deep drawing methods with emphasis on the quality of deep drawn products. These methods include hydromechanical deep drawing, micro deep drawing, and deep drawing operation using magnet-rheological medium. This paper also presents challenges and scope of future research leading to commercial implementation of recently developed techniques of deep drawing.